Tata Kelola Organisasi Badan Usaha Milik Desa (BUMDes) Berbasis Potensi Lokal Di Desa Tumiyang Kecamatan Kebasan Kabupaten Banyumas - Ngutsman Mukromin; Chamid Sutikno; Deni Setiawan; Chumedi Yusuf; Tri Wahyu Yuliani (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Village development can be improved by developing the village's economic potential and becoming a forum for rural communities to develop themselves and their environment independently and participatively. One new approach that is expected to be able to drive development and drive the village economy is through the establishment of village community economic institutions called Village-Owned Enterprises (BUMDes) as one of the mainstay programs in increasing village economic independence. This service activity aims to analyze and describe in depth the management of village-owned enterprises (BUMDes) in Tumiyang Village, Kebasen District, Banyumas Regency. After analyzing the problem, aspects of BUMDes institutional assistance activities can be determined. Asepk, which is the focus of implementing this service, focuses on organizational management and governance which looks at BUMDes development from the aspects of planning, organizing, and directing in carrying out the functions and responsibilities of managing village-owned enterprises (BUMDes).